Tradition and Modernity in Shashi Tharoor’s The Great Indian Novel - Bhaktipriya Bhargava (Integrated Journal for Research in Arts and Humanities, 2022)
Tradition nourishes culture and infuses vivacity into modernity. This effort describes how Shashi Tharoor has used myth to combine tradition with modernity to delineate essential practices of Indian civilization in The Great Indian Novel. Accordingly, this paper attempts to identify his sources and resources in order to underline his novelty, artistic imagination, and at times his deliberate deviations in interpretation of customary legacies. The use of symbols, motifs, and allusions has been highlighted to project amalgamation of tradition and modernity. The motive has been to appreciate the depiction of traditional Indian bearings and bring out essential norms, practices, belief, and rituals pertaining to Indian civilization. A note of criticism lurks in to discard descriptions describing distorted realities.